Validation of the Bahasa Malaysia version of the Coping Inventory for Stressful Situation (CISS) - Musa, Ramli; F., Mohd Ariff; Y., Khalid; S., Rosnani (Malaysian Journal of Psychiatry, 2008)
Introduction: There is an appealing need to have a validated Bahasa Malaysia (BM) questionnaire that is able to gauge stress coping styles among Malaysian population. A culturally accepted questionnaire will generate further research in the aspect of stress coping patterns in the Malaysia population. Objective: To translate the Coping Inventory for Stressful Situations (CISS) questionnaire into BM and to determine the construct validity, reliability and other psychometric properties of the translated BM version of the English CISS 48-item. Method: Two parallel forward and backward translations were done in BM in accordance to guideline and its validation was determined by using confirmatory factor analysis among 200 Malaysian subjects. Results: The BM CISS had very good Cronbach’s alpha values, 0.91, 0.89 and 0.85 respectively for Task-, Emotional- and Avoidance-oriented. The overall Cronbach’s alpha was 0.91. It also had good factor loading for most of its items where 44 items out of 48 had Confirmatory Factor Analysis values of more than 4.0. Conclusions: BM CISS had been adequately and correctly translated into Bahasa Malaysia with high psychometric properties. Minimal readjustment may be required in a few of its items to obtain excellent results.